2015
DOI: 10.3390/en8021166
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Pretreatment of Boreal Aspen Woodchips in a Pilot Scale Digester

Abstract: Hot water extraction of aspen woodchips was treated at about 160 °C for 2 h with a liquor-to-solid ratio of 4.76:1 in a 1.84 m 3 batch reactor with external liquor circulation. Both five-carbon and six-carbon sugars are obtained in the extraction liquor. Xylose and xylooligomers are the main five-carbon sugar in the hot water extract, which reached a maximum concentration of 0.016 mol/L, and 0.018 mol/L, respectively. Minor monosaccharides including galactose, mannose, rhamnose, glucose, and arabinose are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…In the current study, conversion efficiencies were found maximum for shorter pretreatment time (5 min). High residence time at elevated temperatures during pretreatment led to high pretreatment severity and produced several compounds inhibitory to enzymes and yeasts [38,39]. Weil et al [9] found that improvement in hydrolysis efficiency of corn fiber decreased with increase in pretreatment severity.…”
Section: Effect Of Hot Water Pretreatment On Fiber Conversionmentioning
confidence: 99%
“…In the current study, conversion efficiencies were found maximum for shorter pretreatment time (5 min). High residence time at elevated temperatures during pretreatment led to high pretreatment severity and produced several compounds inhibitory to enzymes and yeasts [38,39]. Weil et al [9] found that improvement in hydrolysis efficiency of corn fiber decreased with increase in pretreatment severity.…”
Section: Effect Of Hot Water Pretreatment On Fiber Conversionmentioning
confidence: 99%
“…For example, from woody biomass, hot water extraction in a pilot-scale allowed to achieve high release of glucose and xylose mainly originated from hemicellulose and also xylose oligomers. Reducing extraction time helped to limit sugars degradation although decreasing sugar yields (Yan and Liu, 2015; Yan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This pretreatment shows great potential for degrading lignocellulosic material thus making it easily accessible to enzymes by disrupting the interpolymeric association between lignin, hemicellulose, and cellulose [51]; and this leads to minimal production of potentially inhibitory products [52]. Chen et al [53], in their work on the investigation of the degradation of carbohydrates and lignin of the aspen wood during hot water extraction, show that the degradation of xylose did not occur until 150 • C. Kilpelainen et al [54] who worked on extraction of birch sawdust using pressurized hot water, reported only trace amounts of furfurals in the extracts after heat treatment at 150 to 160 • C. The amount of hydroxymethyl furfural (HMF) was under 6 µg/L for all extraction temperatures between 150 and 190 • C. However, no furfural or HMF was detected in hot water pretreatment of boreal aspen woodchips at 160 • C and 210 Min [55].…”
Section: Figmentioning
confidence: 99%